2008
DOI: 10.1002/rra.1187
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partial removal of the invasive macrophyte Lagarosiphon major (hydrocharitaceae) on invertebrates and fish

Abstract: Invasive macrophyte species are a threat to native biodiversity and often grow to nuisance levels, therefore, making control options necessary. Macrophyte control can have pronounced impacts on littoral fish by reducing habitat heterogeneity and the loss of profitable (high density of invertebrates) foraging areas. Yet, there is little known about the impacts of macrophyte removal on invertebrates themselves. We conducted a macrophyte removal experiment, that is the cutting of channels into dense macrophyte be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Reduced taxonomic richness was found in a study covering a single river in Australia (Carey et al, 2018), while other studies in lakes and rivers did not find changes in richness (Bickel and Closs, 2009;Ward-Campbell et al, 2017). Shannon-diversity was shown to increase in a study in a river in the U.S. (Lusardi et al, 2018), while other studies in rivers did not detect a change in Shannondiversity (Buczyński et al, 2016;Dabkowski et al, 2016).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Reduced taxonomic richness was found in a study covering a single river in Australia (Carey et al, 2018), while other studies in lakes and rivers did not find changes in richness (Bickel and Closs, 2009;Ward-Campbell et al, 2017). Shannon-diversity was shown to increase in a study in a river in the U.S. (Lusardi et al, 2018), while other studies in rivers did not detect a change in Shannondiversity (Buczyński et al, 2016;Dabkowski et al, 2016).…”
Section: Introductionmentioning
confidence: 80%
“…Studies have shown reduced macroinvertebrate abundance after macrophyte removal in rivers (Grygoruk et al, 2015;Känel et al, 1998) and lakes (Habib and Yousuf, 2014;Miliša et al, 2006), while others demonstrated neutral (Buczyński et al, 2016;Ward-Campbell et al, 2017) or even positive (Bickel and Closs, 2009) effects of plant removal on macroinvertebrate abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, these effects can be both positive and negative. For example, Dawson et al ( 1991 ) reported a case where 30 macroinvertebrate individuals were removed per gram dry weight of cut aquatic plants, while Bickel and Closs ( 2009 ) showed that total invertebrate biomass and abundance was significantly higher in the areas where mowing took place compared to the untreated macrophyte beds. Moreover, while Engel ( 1990 ) reported that up to 450 fish were removed per 100 kg fresh weight of cut aquatic plants, the potential for improving growth and size structure of fishes by reducing macrophyte density has long been recognized (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These dense stands of aquatic plants cause nuisance to bathers and swimmers, which generally dislike the touch of plants and because invertebrates living on the macrophytes may cause itches and rash of the human skin (Van Donk 1990 ). Dense stands can also cause nuisance for fisherman as lines easily get stuck and because a high macrophyte cover can have a negative effect on fish abundance (Bickel and Closs 2009 ). Moreover, dense stands can impair (recreational) boat traffic and can decrease lakefront property values.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty is increased by the possibility that some invasions may result in neutral (or even benign) effects on ecosystems (Thomaz & Cunha, 2010;Schlaepfer, Sax & Olden, 2011). For example, non-native Lagarosiphon major and Elodea canadensis (Hydrocharitaceae) in an alpine lake in New Zealand were associated with increases in epiphyton, benthic invertebrate diversity and abundance of a native fish (Kelly & Hawes, 2005); Lagarosiphon major also appears to provide highly suitable habitat for fish in an altered reservoir system which is largely devoid of native plants (Bickel & Closs, 2009).…”
Section: Introductionmentioning
confidence: 99%